Predicting the influence of travel web site effectiveness characteristics on technology acceptance and its marketing implications - Norzalita Abd Aziz; Ainin Sulaiman; Ghazali Musa (Penerbit Universiti Kebangsaan Malaysia, 2008)
There is a growing reliance on web sites of tourism and travel related product/services promotion. The Internet or web site can be a powerful tourism communication tool if used in a proper way. Thus, identification of travel web site effectiveness characteristics based on travellers/internet users' expectation is necessary. This paper explores the travel web site effectiveness characteristics and their relationships with the extrinsic motivation and intrinsic motivation of technology acceptance. Here, an attempt is made to explain internet users' beliefs using Technology Acceptance Model with data collected from 679 internet users/travellers. Factor analysis reveals three dimensions of travel web effectiveness characteristics were derived, namely: 1) Technical Adequacy & Customization. 2) System Quality & Specific Content and 3) Web Appearance. Additional procedures are employed in order not to violate the assumptions of the mUltiple regressions. Tabachnick and Fidell (2007) suggested that if there is very strong correlation between independent variables with r value more than 0.75, there is a need to drop one of the variables or forming a composite variable. The correlation between Technical Adequacy & Customization and System Quality & Specific Content is high (r = 0.79). Thus, a new composite variable is created by taking the mean values of both variables. The new variable is labelled as Technical Adequacy & System Quality. The multiple regression results show that Travel Web Site Effectiveness Characteristics have direct influence on Extrinsic Motivation and Intrinsic Motivation of technology acceptance. However, Technical Adequacy & System Quality is more influential in explaining Extrinsic Motivation and Intrinsic Motivation with beta value higher than Web Appearance.